2021
DOI: 10.1080/07853890.2021.1931956
|View full text |Cite
|
Sign up to set email alerts
|

Association of immune-related adverse events induced by nivolumab with a battery of autoantibodies

Abstract: Background The aim of this study was to assess the diagnostic performance of an autoantibody battery in patients receiving immune checkpoint inhibitors who experienced immune-related adverse events (irAEs). Methods We retrospectively analyzed several variables potentially related to irAEs, namely, demographic, clinical, and laboratory characteristics, including an autoantibody battery (antinuclear, anti-neutrophil cytoplasmic, anti-thyroid antibodies and rheumatoid fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Autoantibody presence might be associated with a higher rate of irAEs and possibly better survival outcomes in patients with NSCLC and solid-organ cancers who are treated with ICIs. 5 , 6 This is consistent with the severe irAEs and marked, durable response that we observed in our patient after only one cycle of atezolizumab. Nevertheless, the autoantibody type and levels that are associated with ICI safety and efficacy remain unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Autoantibody presence might be associated with a higher rate of irAEs and possibly better survival outcomes in patients with NSCLC and solid-organ cancers who are treated with ICIs. 5 , 6 This is consistent with the severe irAEs and marked, durable response that we observed in our patient after only one cycle of atezolizumab. Nevertheless, the autoantibody type and levels that are associated with ICI safety and efficacy remain unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we propose different mechanisms related to cardiac irAEs, such as autoantibody production. Autoantibodies induced by ICI therapy include anti-acetylcholine receptors, striated muscle, mitochondria, alanyl-tRNA synthetase, SRP-B, and 3-hydroxy-3-methylglutaryl-coenzyme, these autoantibodies were found too in a recent systematic review published by ( Ghosh et al, 2022 ), and despite that, we did not study the association of ICI-induced autoantibodies and anti-cancer efficacy, where some authors propose that the irAEs are associated with better antitumoral effect or trend for better survival ( de Moel et al, 2019 ; Les et al, 2021 ). Furthermore, the recent finding by Bocksthaler et al, 2021 showed that Troponin I (TnI)-directed autoimmune myocarditis (TnI-AM) is mediated by CD4 + T-cells, and the immunoproteasome is a key player in this autoimmunity.…”
Section: Discussionmentioning
confidence: 75%
“…Second, as in certain autoimmune diseases, some irAEs may be not ANA-related but rather due to cell-mediated immune mechanisms or autoantibody-mediated mechanisms different from ANA [ 35 ]. In line with this second reason, other authors have correlated the presence of autoantibodies with higher irAE rates [ 36 , 37 ], though these studies considered a broader spectrum of different autoantibodies, not specifically ANAs, which may explain the different results.…”
Section: Discussionmentioning
confidence: 81%